PROMOÇÃO DA SAÚDE ATRAVÉS DA REALIDADE VIRTUAL: CONTRIBUIÇÕES DA EXTENSÃO UNIVERSITÁRIA - DUARTE DIAS, ISABELA; MENDES VIDAL, KAROLYNE KELLEN; MORAIS FERNANDES DE OLIVEIRA, LORENA; DE CASTRO ELEUTÉRIO , LUCAS; GOIS SANTOS JARDIM, LUIZ GUSTAVO; DOS SANTOS, MARIA LUIZA; DE SOUZA DINIZ , RAMON; TEIXEIRA BARRAL DE LACERDA, TATIANA (Sinapse Múltipla, 2019)